2010
DOI: 10.1128/jcm.01579-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Tests for Clostridium difficile Infection

Abstract: We evaluated toxigenic Clostridium difficile detection by a lateral flow assay for antigen and toxin, an enzyme immunoassay, and two commercial PCR methods. Compared to the cell cytotoxicity neutralization assay and toxigenic culture, both toxin detection methods lacked sensitivity. PCR following combined antigen and toxin detection provided the most useful diagnostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 14 publications
14
102
2
2
Order By: Relevance
“…Several reports have documented poor analytical sensitivity of toxin immunoassays in comparison to toxigenic culture and/or various PCR-based assays. [4][5][6][7][8][9][10] The present study supports those findings. Coupled with the fact that many laboratories still use the relatively low-cost toxin EIA as the primary method for laboratory diagnosis, 11,12 medical providers may frequently face the decision whether to initiate therapy in the absence of laboratory confirmation or to repeat laboratory tests.…”
Section: Commentsupporting
confidence: 82%
See 1 more Smart Citation
“…Several reports have documented poor analytical sensitivity of toxin immunoassays in comparison to toxigenic culture and/or various PCR-based assays. [4][5][6][7][8][9][10] The present study supports those findings. Coupled with the fact that many laboratories still use the relatively low-cost toxin EIA as the primary method for laboratory diagnosis, 11,12 medical providers may frequently face the decision whether to initiate therapy in the absence of laboratory confirmation or to repeat laboratory tests.…”
Section: Commentsupporting
confidence: 82%
“…Recent investigations have focused on real-time PCR as a candidate for GDH screen confirmation. Using the same GDH assay described here, Sharp et al 21 and Swindells et al 8 reported excellent performance characteristics of a two-step GDH-PCR algorithm. They observed ,100% sensitivity of the GDH screen component compared with toxigenic culture and/or PCR, as well as excellent correlation between second-step PCR testing and toxigenic culture results.…”
Section: Commentmentioning
confidence: 99%
“…26 In addition, the actual date and time at which C. difficile was acquired is likely earlier than the date/time of the positive test result (the date/time used in our study). Therefore, the time from acquisition to discharge for our cohort may be underestimated.…”
Section: Limitationsmentioning
confidence: 93%
“…This is consistent with the results of several reports. [7][8][9][10] Although CCCN is recommended in the SHEA-IDSA guidelines, 1 this approach is less desirable as a reflex test because of its reduced sensitivity compared with NAATs and toxigenic culture and, from a more practical standpoint, because of its general lack of availability in most hospital laboratories. Although reflex testing using toxigenic culture produces statistically equivalent sensitivity and specificity to NAAT reflex testing, the delay in finalizing results would likely have a negative impact on both infection control costs and, potentially, on the initiation of therapy for patients with CDI.…”
Section: Effect Of Various Testing Algorithms On Isolation Of Patientmentioning
confidence: 99%